TINGKAT PENDIDIKAN, UPAH, INFLASI, DAN PERTUMBUHAN EKONOMI TERHADAP PENGANGGURAN DI INDONESIA - Indra Suhendra; Bayu Hadi Wicaksono (FEB Universitas Sultan Ageng Tirtayasa, 2016)
The aim of this study is to determine the influence of education level, wages, inflation, andeconomic growth to unemployment rate in Indonesia during the Period of 2010 to 2012. Paneldata regression analysis model is conducted as the research model. The research results showsthat during 2010 to 2012, educations level in bachelor degree (TPS1), wages, inflation andeconomic growth have significant effect to unemployment rate, whereas education level insenior high school (TPSMA) has not significant influence to unemployment rate. Simultaneouslythe independent variables have significant influence to the dependent variable. The coefficientof determination (R2) shows 0.722353, meaning that the variasion of dependent variable canbe explained by the variasion of independent variables as many as 72.2353 percent .